HUBUNGAN MINAT MEMBACA DENGAN KEMAMPUAN MENULIS CERITA PENDEK SISWA KELAS XI SMK SWASTA SWAKARYA BINJAI TAHUN PELAJARAN 2020/2021 - Jepri Arizal; Sintia Ramadhani (Jurnal Analisa Pemikiran Insan Cendikia (Jurnal APIC), 2022)
The Relationship between Reading Interest and Short Story Writing Ability by Grade XI Students of Swakarya Binjai Vocational School for the 2020/2021 Academic Year. This study aims to determine the correlation between interest in reading and the ability to write short stories by class XI students of SMK Swakarya Binjai for the 2020/2021 academic year. The sample of this research was class XI AK totaling 19 people. This type of research is quantitative with a correlation (relationship) between one variable and another. Based on the results of data analysis, it can be concluded that there is a relationship between reading interest and the ability to write short stories for class XI students of Swakarya Binjai Vocational School for the 2020/2021 academic year as indicated by the value of rcount > rtable, namely 0.977 > 0.368.